2018
DOI: 10.1007/s00382-018-4266-4
|View full text |Cite
|
Sign up to set email alerts
|

Subseasonal intensity variation of the South Asian high in relationship to diabatic heating: observation and CMIP5 models

Abstract: This study investigates the subseasonal intensity variation of South Asian high (SAH) and the dynamic linkage with precipitation induced diabatic heating during the summer of 1979-2005, based on the observation and 18 models from the Coupled Model Intercomparison Project (CMIP5). The SAH's intensity variation with a period of approximately 10-36 days is identified both in the observation and 18 models, by performing an empirical orthogonal function (EOF) analysis on the standardized subseasonal anomalies in ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…In this study, we use daily precipitation, SLP, geopotential height (Z), zonal wind field (U), meridional wind field (V), and specific humidity (q) from the historical run experiments from 14 models in CMIP5, assessing whether these models can capture the relationship between heavy precipitation events and large‐scale climate modes (i.e., AO, NAO, EA, and SCAND) in observations across Europe. The relationships between heavy precipitation events and large‐scale climate modes are computed for E‐OBS and for each model on their original spatial resolutions; the results from GCMs are then interpolated to E‐OBS's grid to the comparison (e.g., Jiang et al ., 2015; Shang et al ., 2019). For each of the CMIP5 GCMs, we only consider the first member.…”
Section: Datamentioning
confidence: 99%
“…In this study, we use daily precipitation, SLP, geopotential height (Z), zonal wind field (U), meridional wind field (V), and specific humidity (q) from the historical run experiments from 14 models in CMIP5, assessing whether these models can capture the relationship between heavy precipitation events and large‐scale climate modes (i.e., AO, NAO, EA, and SCAND) in observations across Europe. The relationships between heavy precipitation events and large‐scale climate modes are computed for E‐OBS and for each model on their original spatial resolutions; the results from GCMs are then interpolated to E‐OBS's grid to the comparison (e.g., Jiang et al ., 2015; Shang et al ., 2019). For each of the CMIP5 GCMs, we only consider the first member.…”
Section: Datamentioning
confidence: 99%
“…In our prior work, Shang et al . () suggested that strengthening of the SAH is accompanied by above‐normal precipitation in the Asian monsoon regions. However, how and to what extent the SAH may exert influence on the PHR events is unclear and the difference between the influence of SAH on the different threshold PHR events has not been assessed in detail yet.…”
Section: Introductionmentioning
confidence: 99%
“…The establishment of the SAH and the associated meridional movement of the ridgeline have close relationships with the onset of the Asian summer monsoon [3][4][5] and location of rain belt over East China 6,7 . Changes in the SAH have notable impacts on the weather and climate in many regions, such as precipitation over China [8][9][10][11] , India [12][13][14] , and the Korean peninsula [15][16][17][18] . The SAH can also impact precipitation and surface temperature over the North Pacific and North American regions by modulating atmospheric teleconnection patterns 19 .…”
mentioning
confidence: 99%